Effect of annealing temperature on structural, optical and photocatalytic properties of α-Fe2O3 nanostructures. Issue 10 (3rd October 2018) - Singh, Sandhya; Hitkari, Gaurav; Pandey, Gajanan
Abstract: In the present work α-Fe2 O3 nanostructures have been synthesized by chemical co-precipitation followed by annealing at 500 and 600 °C for 3 h. Nanostructure powders were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FT-IR), particle size distribution, Brunauer Emmett Teller analysis (BET), photoluminescence and UV-visible spectroscopy. XRD confirmed the formation of crystalline α-Fe2 O3 nanostructures while SEM confirmed the formation of rice grain and spherical shape α-Fe2 O3 nanostructures at 500 and 600 °C annealation temperature. From EDX and FTIR results formation of α-Fe2 O3 is further established. BET analysis confirmed the mesoporous behavior of nanostructures. UV-Visible and photoluminescence spectra have been used to determine band gap and photo-oxidation behavior of dye methylene blue. Both α-Fe2 O3 -500 and α-Fe2 O3 -600 nanostructures exhibit exceptionally high photocatalytic activity however the same is higher for α-Fe2 O3 -500 than that of α-Fe2 O3 -600 for degradation of methylene blue (Meb).